Incidence, Depth and Severity of Poverty in Geidam, Yobe State, Nigeria: Foster, Greer & Thorbecke Analysis - Sani, Audu; Salisu, Lawan Nasiru; Kalli, Fatimah Ba’aba; Geidam, Karagama Kolo (Kashere Journal of Management Sciences, 2024)
This study assessed the Incidence, Depth, and Severity of Poverty in Geidam, Yobe State, Nigeria. The paper dwelled extensively on the point-in time poverty (current poverty) and the three (3) components that made it; these are: the incidence of poverty (head count ratio), Depth of poverty (poverty gap) and severity of poverty (poverty gap squared). Using a primary data (from a well structured questionnaire); The study employs a multi-stage random sampling techniques to selects 25 respondents from each of the randomly selected four wards of Geidam local government area namely; Asheikiri, Hausari, Kalgeri/Jororo, and Gumsa. Finally a total of one hundred (100) respondents/households’ heads was selected for the study. Descriptive statistics of the respondents, and the Foster, Greer and Thorbecke (FGT) index analysis were used to analyze the incidence, Depth and severity of poverty in the study area. The study results reveal that: head count ratio, poverty gap and poverty gap squared in the local government area are high and stand at 63.67%, 28.39%, and 12.66% respectively. The study recommends the provision of comprehensive and integrated safety nets to the study area, in order to build their capacities and increase their incomes for smooth growth and development.